"Extra marginalisation within the community": queer individuals' perspectives on suicidality, discrimination and gay pride events. Issue 1 (2nd January 2019) - Schimanski, Irie David; Treharne, Gareth J.
ABSTRACT: Suicidality is more common among queer individuals. Past research has overlooked queer individuals' own understandings of suicidality in relation to discrimination and supportive processes potentially achieved through gay pride events. This study applied the decompensation model as a framework to explore queer individuals' perceptions of suicide, discrimination and gay pride events. Seven focus groups were held with a total of 28 queer individuals aged 18–25 years old. Participants had a range of sexualities, genders and ethnicities. Qualitative data from the focus groups were interpreted using an inductive form of thematic analysis, resulting in three themes: the invisibility of suicide; compound discrimination ; and processes of normalising queer identities . Participants suggested that greater awareness of suicide is needed and proposed a trajectory from discrimination to suicide, wherein both queer identities and suicidality are discriminated against. Discrimination from within queer communities was problematised and gay pride events were understood to normalise queer identities by providing opportunities for support and fostering activism against inequalities. The results underscore nuanced perspectives on suicidality, discrimination and gay pride events among young queer individuals in Aotearoa/New Zealand and have implications for suicide prevention efforts. These findings also demonstrate the value of applying an intersectional approach to identity, ideology and discrimination in research on suicidality among queer individuals.